Effectiveness and safety of infliximab in cardiac Sarcoidosis. (1st May 2021) - Bakker, A.L.M.; Mathijssen, H.; Azzahhafi, J.; Swaans, M.J.; Veltkamp, M.; Keijsers, R.G.M.; Akdim, F.; Post, M.C.; Grutters, J.C.
Abstract: Background: Immunosuppressive therapy in active cardiac sarcoidosis (CS) might prevent potential life-threatening complications. Infliximab (IFX) is a tumor necrosis factor alpha monoclonal antibody proven to be effective in refractory extracardiac sarcoidosis. It is sparsely used in CS, because of its association with worsening heart failure in prior studies. The goal of this study is to assess the effectiveness and safety of IFX in CS. Methods and results: A retrospective, single center cohort study was performed in sarcoidosis patients treated with IFX based on a cardiac indication between January 2016 and March 2019. Patients received IFX intravenously at a dose of 5 mg/kg at week 0, 2, and subsequently every 4 weeks. After every six months, treatment response was evaluated within the multidisciplinary team using FDG-PET/CT, transthoracic echocardiography, biomarkers and device interrogation reports. Responder analysis definitions were based on; dosage of immunosuppressive drugs, improvement in functional class, left ventricular ejection fraction (LVEF) and SUVmax. Twenty-two patients were included (mean age 51.0 SD10.0 years, male 68.2%) with a mean follow-up of 18.9 months (6 to 44 months) of whom 18 (82%) were classified as responders. Median SUVmax on FDG-PET/CT decreased from SUVmax 5.2 [3.7–8.4] to 2.3 [1.4–2.3], p = 0.015. The target-to-background ratio decreased from 3.2 [2.1–5.1] to 1.0 [0.7–2.4], p = 0.002. The median left ventricular (LV) ejection fraction increased from 45.0% [34.0–60.0] to 55.0% [41.0–60.0], p = 0.02. The majority of patients (73%) experienced no side effects and no patients had worsening of heart failure. Conclusion: In this pilot study, patients with refractory CS treated with infliximab, on top of standard of care, had a reduction in inflammation on FDG-PET/CT and an improvement in LV function, without serious adverse events. Highlights: Immunosuppressive therapy in active cardiac sarcoidosis might prevent potential life-threatening complications Infliximab has proven to be effective in refractory extra-cardiac sarcoidosis, but has been sparsely used in cardiac sarcoidosis Ii IAfter After treatment with Infliximab in refractory CSon top of standard of care, showed a reduction in inflammation on FDG-PET/CT and an improvement in LV function, without serious adverse events.